A unique copper coordination structure with both mono- and bi-dentate ethylenediamine ligands. Issue 17 (12th March 2019) - Sharma, Jai; Jiang, Zhelong; Bhutani, Ankita; Behera, Piush; Shoemaker, Daniel P.
Abstract : A new crystal structure achieving penta-coordination using exclusively ethylenediamine ligands is discovered and characterized. Abstract : The compound (ethylenediamine- N )-bis(ethylenediamine- N, N ′)-copper(ii ) bis(nitrate) is reported. It has an asymmetric unit containing Cu(ii ) penta-coordinating to two chelating ethylenediamine (en) and one monodentate en ligands with square-pyramidal-based geometry having severe trigonal distortion, together with two nitrate anions. It is the first crystallographic confirmation of the existence of penta-coordination with exclusively en ligands for any metal center, as well as the first monodentate en attached to Cu(ii ) seen in the solid state. It can be visualized as the penta-ammine effect realized solely with bi-amine ligands, defying the presumed necessity of mono-amines. X-ray crystallography establishes it to have P 21 / c space group with a = 12.83 Å, b = 9.77 Å, c = 11.91 Å, and β = 94.8° (at 100 K). Spectroscopic analysis of this compound is consistent with the crystallographic assessment of the coordination chemistry, and it is found to be a S = 1/2 paramagnet.